Probiotics for the Management of Infectious Diseases: Reviewing the State of the Art - Wiegers, Cato; van de Burgwal, Linda H. M.; Larsen, Olaf F. A. (Frontiers in Microbiology, 2022)
This review aims to provide insight into the potential of probiotics as a clinical modality targeted at infectious diseases by creating a comprehensive overview of the state of the art of research and development efforts as shown by patents and clinical trials of the past 20 years. Data was retrieved from patent and clinical trial databases to reflect the long- and short-term developments of probiotics research. The data was analyzed to extract information on the total number of patents and trials for each indication, application date and location, and applicant/sponsor type. A total of 80 infectious diseases were investigated, precipitating in 789 patents and 602 clinical trials for 67 indications studied as targets of probiotics. An increasing trend was seen for the number of patents and clinical trials that were applied for since 1999 with the highest number of patents and clinical trials targeted to digestive tract, respiratory and urogenital indications. Overall, research demonstrated a substantial interest in probiotics targeting infectious diseases, which was in line with reported unmet needs and global probiotics sales estimates. However, the declining rate of translation from patents to clinical trials indicates that there are some barriers obstructing the research process.